Women who prefer "lesbian" to "queer": generational continuity and discontinuity. Issue 1 (1st July 2021) - Megarry, Jessica; Weiss, Catherine Orian; Tyler, Meagan; Farhall, Kate
ABSTRACT: The legitimacy of the term and identity "lesbian" has long been contested, but has come under renewed scrutiny, with some suggesting it is exclusionary and dated. Along with these suggestions is the implication of a generational divide. Supposedly, older women—unaware of contemporary queer discourses—are more likely use the term "lesbian, " whereas younger women are more likely to choose queer affiliated identities. In this paper we draw on survey data investigating why some women might seek to retain the identity "lesbian." These narratives complicate simplistic accounts of a generational divide. We discuss themes of cross-generational continuity in participants' sense of historical connection; connection to politics; lesbian visibility; and specificity and boundaries. The theme of lesbian community demonstrated discontinuity: participants of all ages agreed on the importance of lesbian community, but there was generational discontinuity in the access that participants had to it. Our respondents were aware of, and reflective about, current debates situating the category "lesbian" as problematic or obsolete, and nonetheless found utility and meaning in the term. Through their analysis we hope to destabilize discussions about a generational divide defining the use of the term "lesbian" with corresponding questions around ongoing relevance.